The Effect of Cognitive-Behavioral Therapy-based Social Work Intervention on the Burden of Formal Caregivers Among Alborz City Nursing Home - Hakime Pashazade; Yadollah Abolfathi Momtaz; Ghonche Raheb (Iranian Rehabilitation Journal, 2022)
Objectives: As the elderly population increases, the need for their care and establishing nursing homes and hiring formal caregivers becomes more significant. Caregivers are under the pressure and burden of care due to the provision of services. The current study investigates the effect of Cognitive-Behavioral Therapy (CBT)-based social work intervention on the extent of care burden among the formal caregivers of the elderly. Methods: This research was a quasi-experimental study with a pretest-posttest-follow-up design. The study’s statistical population comprised the formal caregivers of the elderly. The study sample consisted of 30 caregivers (15 men and 15 women), who were selected by convenience sampling method. The study participants received seven 90-min intervention sessions (CBT-based social work). The intervention protocol was validated by the Agree form using expert opinion evaluation. For data collection, the Zarit caregiver burden interview (short-form) was used. This scale has been validated by Rajabi Mashhadi et al. (2014) in Iran. Results: The care burden score of the explored participants was 24.20, within the average level. The repeated-measures analysis of variance revealed that the presented intervention provided a significant difference between the two stages of pretest and posttest in physical (P=0.004) and psychological (P=0.05) dimensions. Also, the changes in the study variables remained constant until the follow-up stage. Discussion: The obtained data indicate that the provided CBT-based social work intervention with the dimensions of identifying and accessing supportive resources, modifying attitude, and relaxation training can reduce the burden of care in physical, psychological, and general aspects among the study subjects. Therefore, more use of this intervention by specialists can affect the care burden of formal caregivers. The present research results also highlight the necessity for the attention of nursing home officials, social policymakers, and professionals active in the field of elderly care.